CASPR2 antibody encephalitis presenting as transient epileptic amnesia. (October 2020) - Cretin, Benjamin; Bilger, Mathias; Philippi, Nathalie; Blanc, Frederic
Highlights: Isolated transient amnesia can be of epileptic origin. The epileptic origin may be suggested by a short duration of the episodes (< 1 h). Interictal cognitive complaints are highly suggestive of the diagnosis. Both interictal and ictal features can be of autoimmune origin (here, anti-CASPR2).